Models for Decision Making in Organizations and Some Contextual Variables Which Stipulate Optimal Use - Nutt, Paul C. (Academy of Management Review, 1976)
Six organizational decision making models are described and critiqued. It is postulated that an optimum model can be selected by considering: dependencies among organizational units and layers, key tasks of each unit, performance assessment between adjacent layers, and environmental characteristics.